Physical oceanography during Alkor cruise AL614 - Luisa Listmann (PANGAEA, 2025)
This data set comprises unprocessed CTD data collected during the RV ALKOR cruise AL614 cruise conducted in June 2024 (6th to 15th of June) in the Western Baltic Sea by the University of Hamburg. The cruise was part of the 5-year MARSYS teaching cruise program of the University of Hamburg GFP20-1_047. The cruises are designed to train students in sampling methods targeting the different compartments of a marine ecosystem. The CTD data was obtained directly from the Sea & Sun Technology software. No quality control of the data has been done.